The Travels of Ibn Battuta, A.D. 1325-1354. - Ibn Batuta, 1304-1377 (Routledge, 2006)
Ibn Battuta was born in Tangier in 1304. Between 1324 and 1354 he journeyed through North Africa and Asia Minor and as far as China. On a separate voyage he crossed the Sahara to the Muslim lands of West Africa. His journeys are estimated to have covered over 75,000 miles and he is the only medieval traveller known to have visited every Muslim state of the time, besides the 'infidel' countries of Istanbul, Ceylon and China. This first volume records the earliest journeys through Tunisia, Egypt, Syria, Arabia, on pilgrimage to the Holy Places of Islam. Among the detailed descriptions of towns on the road and of their inhabitants, he gives a particularly circumstancial account of Medina and Mecca.